Knowledge, risk attitudes and perceptions on extreme weather events on smallholder farmers in Ligao City, Albay, Bicol, Philippines - Peria, Aileen S. (Journal of Environmental Science and Management, 2016)
Smallholder farmers in the Philippines, whose survival and livelihood largely depend on the environment, constantly face risks and bear the impacts of the changing climate. This paper explored how climate change knowledge as well as attitudes and perceptions to risk of smallholder farmers from upland, lowland and coastal ecosystems influence the manner on which they respond and cope with extreme events. Guided by the Adaptation Policy Framework, a questionnaire was developed and administered to 313 smallholder farmers to determine the kind of information that farmers have and how they respond to climate risks towards enhanced adaptive capacity. Seventy-nine percent of respondents lack basic knowledge on climate change. Majority (79%) of respondents recognised that they are exposed to extreme weather risks and perceived climate as a major farming risks. However, availability and access to capital (not climate change) is the biggest perceived threat. Sixty-nine percent of respondents are risk-takers. Based on correlation, attitudes on risk are influenced by exposure, economic factors and availability of resources. This paper recommends a more targeted climate change information dissemination and customised trainings that enhance capacity, improve livelihood choices and conserve the natural resources.